Emptying Subjects with Legal Impact Forensic Linguistic Studies - Teddy Yusuf; Aceng Ruhendi Syaifullah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article discusses the problem of subject omission conducted by the Governor of DKI Jakarta, Ahok Cahya Purnama. In this writing, the author uses two approaches: the European structural approach and the American structural approach. Ferdinand de Saussure, the first figure from Europe, conducted studies on language with scientific and codified principles, enabling the analysis of active and passive sentences using a systematic method. The Transformational Generative Theory, pioneered by Noam Chomsky as the second figure, was born in 1928 in Pennsylvania, United States. This writing attempts to outline a form of surface structure approach through the analysis of the relationship between elements or Saussure's structuralism, while also using the deep structure approach proposed in Noam Chomsky's Transformational Generative Theory. This is expected to complement Saussure's structuralism approach to enrich the previously used approach and avoid being fixated on a single type of approach. Thus, it can provide a better and more targeted interpretation of ambiguous sentences. Consequently, this article finds that Mr. Ahok has omitted the subject, resulting in ambiguous sentences. The subject in question is the politicians from religious groups who have used Surah Al-Maidah verse 51 as a political tool to win the regional elections.